2019
DOI: 10.3390/md17060348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorella Pyrenoidosa Protein Hydrolysate-Calcium Chelate on Calcium Absorption Metabolism and Gut Microbiota Composition in Low-Calcium Diet-Fed Rats

Abstract: In our current investigation, we evaluated the effect of Chlorella pyrenoidosa protein hydrolysate (CPPH) and Chlorella pyrenoidosa protein hydrolysate-calcium chelate (CPPH-Ca) on calcium absorption and gut microbiota composition, as well as their in vivo regulatory mechanism in SD rats fed low-calcium diets. Potent major compounds in CPPH were characterized by HPLC-MS/MS, and the calcium-binding mechanism was investigated through ultraviolet and infrared spectroscopy. Using high-throughput next-generation 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 90 publications
(118 reference statements)
2
20
0
Order By: Relevance
“…Recently, it was found that human gut bacteria can synthesize proteinogenic amino acids and produce a range of metabolites via protein fermentation, some known to exert beneficial or harmful physiological effects on the host [77][78][79][80][81][82][83]. It is still in an early stage whether the type and amount of dietary protein consumed affect the diversity and composition of the intestinal microbiota, and the luminal environment of the intestinal epithelium and peripheral tissues on the host health.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that human gut bacteria can synthesize proteinogenic amino acids and produce a range of metabolites via protein fermentation, some known to exert beneficial or harmful physiological effects on the host [77][78][79][80][81][82][83]. It is still in an early stage whether the type and amount of dietary protein consumed affect the diversity and composition of the intestinal microbiota, and the luminal environment of the intestinal epithelium and peripheral tissues on the host health.…”
Section: Discussionmentioning
confidence: 99%
“…Informed written consent was obtained from 100 volunteers. e present study was conducted as a randomized control trial using methods previously reported by Hua et al in 2018 [7,9]. e subjects were given individual ID numbers to assure anonymity.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the acid load imposed by a modern diet is thought to play an important role in the pathophysiology of osteoporosis. Recently, several studies have investigated the effects of nutrients on bone metabolism and bone mineral density (BMD), with the chelation of citric acid receiving attention in this field [6][7][8]. ose studies indicated that the chelating action of citric acid induces an increase in resorption of potassium and calcium (Ca), leading to the induction of beneficial effects toward BMD and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the protective effects of the P. yezoensis peptide PYP15 against dexamethasone-induced myotube atrophy was revealed [3]. The effect of the Chlorella pyrenoidosa protein hydrolysate (CPPH) and Chlorella pyrenoidosa protein hydrolysate-calcium chelate (CPPH-Ca) on calcium absorption and gut microbiota composition was evaluated [4]. It was demonstrated that CPPH-Ca could promote calcium absorption partially through regulating specific gut microbiota and modulating expressions of the calcium absorption-related genes in kidney.…”
mentioning
confidence: 99%
“…It was demonstrated that CPPH-Ca could promote calcium absorption partially through regulating specific gut microbiota and modulating expressions of the calcium absorption-related genes in kidney. Therefore, CPPH-Ca may be used to promote the calcium absorption and reduce the risk of calcium deficiency [4]. Two novel angiotensin-converting enzyme (ACE) inhibitory peptides were identified in the Gracilariopsis lemaneiformis protein hydrolysate.…”
mentioning
confidence: 99%